The Future of Advertising or Whatever We're Going to Call It. Issue 3 (2nd July 2016) - Schultz, Don
Abstract : In this opinion piece, the author speculates on the future of advertising. Arguing that the challenge of predicting the future lies mainly in the lack of an acceptable definition of the field, the author solves that problem by developing a set of postulates to create boundaries for the theory and practice of the discipline. The postulates of the present discipline are used as the base from which the future might evolve. Three scenarios are proposed for the future of advertising: (1) creeping incrementalism, (2) reversal of buyer/seller roles, and (3) reinvention of the field. The author suggests that those scenarios will develop and play out based on the developmental speed and acceptance of the various technologies identified.